Correlation between adenoma detection rate and other quality indicators, and its variability depending on factors such as sedation or indication for colonoscopy - Groza, Andrei Lucian; Ungureanu, Bogdan Silviu; Tefas, Cristian; Miuțescu, Bogdan; Tanțău, Marcel (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is an important worldwide public health burden and colonoscopy is the main diagnostic and most importantly, preventive method. For this reason, many countries have implemented national or regional CRC screening programs. High-quality colonoscopy is a prerequisite to effectively detect premalignant lesions, like adenomas. The quality of colonoscopy is assessed using several quality indicators, the main one being adenoma detection rate (ADR). In Romania, despite CRC having the highest incidence of all cancers, there is no national screening program and quality in colonoscopy is not routinely assessed. We therefore wanted to evaluate the actual level of quality in colonoscopy in a region of Romania. Our study was conducted in two private endoscopy clinics over a period of seven months. 1440 consecutive colonoscopies performed by five physicians were included in the study. We found that the quality level is above the minimum one recommended by international societies and that the ADR calculation method does not significantly influence its value. Furthermore, ADR correlated well with other quality indicators such as polyp detection rate (PDR) and adenoma per colonoscopy (APC). An interesting finding was that ADR was higher among colonoscopies performed without sedation. Thus, our data encourage endoscopists to adopt a sedation-free colonoscopy in their practice without an impact on the quality of the procedure.